2018
DOI: 10.17219/pim/76515
|View full text |Cite
|
Sign up to set email alerts
|

Kheri (Acacia chundra, family: Mimosaceae) gum: Characterization using analytical, mathematical and pharmaceutical approaches

Abstract: Background. Natural polymers have been used in medical, pharmaceutical, cosmetic and food industry. They should be characterized before their possible applications in different industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The polymer was soluble in hot water, swell to form a gel in cold water and insoluble in methanol, ethanol, benzene and acetone. Studies conducted on Artocarpus integer gum performed by Farooq et al and Malviya et al have also shown the same result and hence support this result [ 45 , 46 ].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The polymer was soluble in hot water, swell to form a gel in cold water and insoluble in methanol, ethanol, benzene and acetone. Studies conducted on Artocarpus integer gum performed by Farooq et al and Malviya et al have also shown the same result and hence support this result [ 45 , 46 ].…”
Section: Resultssupporting
confidence: 73%
“…The viscosity of fluid decreases with an increase in temperature. The viscosity of liquid depends upon the strength of the attractive forces between the molecules that directly depends on their composition, shape, size and kinetic energy of the molecules, which directly depend on the temperature [ 46 ]. This is because when the temperature of the system is raised; energy is added effectively which gives the molecules of the liquid the required energy to overcome the intermolecular force.…”
Section: Resultsmentioning
confidence: 99%
“…Microwave-assisted free radical polymerization was carried out to synthesize KGP-g-Am. [10][11][12][13] Briefly, the polysaccharide and acrylamide solutions were prepared by dissolving KGP (1 g) and acrylamide (6 g) in 30 and 25 mL of water, respectively. Acrylamide solution was poured into the polysaccharide and stirred at 200 rpm for 1 h. CAN solution was prepared in water (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…It is also known as hydrocolloids. 10 Kheri plant is widely found in the Gujarat and Rajasthan regions of India. It is used as a substitute for Acacia gum.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the concoction was subjected to rigorous agitation at 10-minute intervals for a duration of 60 minutes, followed by a 24-hour incubation period at ambient temperature. Following a 24-hour period, the quantity of powder was assessed for volume and subsequently utilized to determine the swelling index [11]. The formula 2 is used to determine the sweeling index.…”
Section: Loss On Dryingmentioning
confidence: 99%